Semilobar Holoprosencephaly with Cebocephaly: A Case Report - Jyothish, Jeevan; Das, Rituparna (Journal of College of Medical Sciences-Nepal, 2021)
Holoprosencephaly is a rare congenital malformation affecting 6 to 12:10,000 live-born infants and is characterized by failure of separation of cerebral hemispheres. Recognised associations include midline facial defects - hypotelorism, cyclopia and cebocephaly. We report a case of semilobar holoprosencephaly with cebocephaly that presented at our hospital. This case is a rare presentation of holoprosencephaly along with facial abnormalities. Our case describes nasal and ocular abnormalities associated with holoprosencephaly. This may add new information regarding associated anomalies of holoprosencephaly. There are three categories of holoprosencephaly with alobar holoprosencephaly being the most severe, followed by semilobar holoprosencephaly and lobar holoprosencephaly being the mildest form. In women with a history of holoprosencephaly or holoprosencephaly in the current pregnancy, antenatal workup to rule out fetal chromosomal disorders and metabolic workup for maternal preeclampsia should be done.